Application of an in-house polymerase chain reaction in the laboratory diagnosis of C. Trachomatis - Seadi, Claudete F.; Oravec, Rejane; Posei, Beatriz Von; Cantarelli, Vlademir V.; Rossetti, Maria Lucia (Brazilian Journal of Sexually Transmitted Diseases, 2003)
Introduction: Chlamydia trachomatis is a sexually transmitted baclerium and has the greatest impact on reproductive female tract. Diagnose of the infection is impaired by the fact that most of the limes lhe infeclion is assynptomatic. The polymerase chain reaction (PCR) tesl is more sensiblc than immunodetection tests, however, commercial tesls are costly. Validation of an in-house PCR, on the othcr hand, requires stringent tests and expertise. Objective: Our aim was to study the application of an in-house PCR on endocervical specimens and compare the results with those obtained with com mercial methods. Methods: Sixty-five samples from women referred to a private laboratory with a specific request for C. trachomatis lest by ELISA or from a public health STD clinic were included in this study. The in-house PCR was compared with commercially available test, whose results were used to classify the samples as positive or negative, if both tests gave the same result for a particular sample. Results: The in-house PCR was able to detect 63% and 50% of the positive samples, as defined by ELISA/PCR AmplicorÒ and dircct immunofluorescence/PCR AmplicorÒ, respectively. The best sensitivity was obtained by in-house nested PCR, followed by PCR Amplicor and in-house PCR with one log difference between each test. Conclusion: The application of the in-house PCR shows that is necessary to improve the detection system of amplification in order to make it more sensible. Also, expand the use of current test lo othcr clinicai specimens are important steps to be considered. In spite of the initial cost, to introduce this test is cheaper than using commercial tests.